Targeting the Process of c-MYC Stabilization in Chronic Myelogenous Leukemia - Sunohara, Maxwell (Université d'Ottawa / University of Ottawa, 2017)
Currently there is no curative therapy for Chronic Myelogenous Leukemia (CML), and patients must remain on the current prescribed treatment, tyrosine kinase inhibitors (TKI), indefinitely. Although many patients can survive in the chronic phase of the disease under TKI treatment, some patients do progress to the terminal blast crisis phase of the disease. Patients in this terminal phase do not respond to TKI treatment. We evaluated the therapeutic benefit of targeting the oncogene c-MYC in CML, using the CML cell line K562. This was achieved by inhibiting the enzyme O-linked β-N-acetylglucosamine Transferase (OGT), using two indirect inhibitors 2-deoxyglucose and Azaserine, and the direct inhibitor ST078925. Treatment with these inhibitors resulted in decreased half-life of c-MYC protein in K562, reduced c-MYC protein in K562 cells, and reduced K562 cell growth. Together these results suggest that targeting c-MYC through OGT may be a potential therapeutic option for patients with CML.
Keywords: c-MYC; leukemia; OGT; Chronic Myelogenous Leukemia